Unraveling the Potential of Coconut Shell Activated Carbon for Catalytic Converter Application: A Preliminary Studies of its Optimization through the Assisted of Fuzzy Logic - Taufik Ulhakim, Muhamad; Marbun, Diansyah; Sukarman, Sukarman; Supriyanto, Agus; Suhara, Ade; Ummah, Auliya Rahmatul; Lidiawati, Neng Astri (Jurnal Teknik Mesin Mechanical Xplore, 2024)
Nowadays, researchers focus on developing catalytic converters based on activated carbon (AC) from organic waste to address environmental concerns. This study presents a preliminary investigation into the application of catalytic converters through the synthesis of AC from coconut shells, with optimization achieved through the implementation of fuzzy logic to ascertain the optimal properties of the AC, specifically the activation temperature. The fuzzy logic approach has determined that the optimal activation temperature is 950 °C. The effectiveness of this approach is substantiated by the successful synthesis of AC, as evidenced by XRD, FTIR, and SEM-EDX analysis. The findings indicate that fuzzy logic provides the most accurate activation temperature information, significantly impacting the AC structure. The resulting yield and bulk density values were 26.29% and 0.519 g/ml, respectively. Proximate analysis indicates that the ash content (4.332%), moisture (7.211%), and volatile matter (16.321%) achieve an FCC of 72.136%. The iodine number is a crucial parameter in evaluating the potential application of AC for the catalytic converter. The results demonstrated that the adsorption performance is achieved in 613 mg/g. In conclusion, the AC produced shows considerable potential for use as a catalytic converter. This assertion is substantiated by the successful evaluation of its efficacy in reducing CO and HC, respectively, by approximately 86.04% and 56.79%. To confirm the suitability of the catalytic converter for the vehicle. A series of dynamometer tests were conducted to verify the catalytic converter's performance. The ensuing test results exhibited a decline in torque and power values, yet these measurements remained within acceptable parameters for typical daily utilization.